The Role Of Islamic Religious Education In Shaping Students' Character - Tasya Aulia Rizka; Pratiwi Fadia Sholihah; Nurika Yuni Safara; Muhammad Yusron Maulana El-Yunusi (Wahana, 2024)
One of the most basic pillars of character education is Islamic religious education. One of the tools used in schools to help with character education is PAI material, which grows from the foundation of fostering religious spirit in children. Islamic religious instructors must help previously disadvantaged students change their ways. Therefore, Islamic religious teachers help shape students' personalities through Islamic law and Indonesian norms, in addition to providing religious knowledge. This research consists of studies whose research objects are researched using various library resources, or studies with a technical relationship with the library data collection process. According to the findings of the study, the main goal of pie learning is to help children develop a personality that will manifest itself in their daily behavior and mentality. In addition, Islamic religious instructors have a great impact on students' achievement and personality development because they support or act as role models for the use of personality formation in the classroom.